Hubungan Kontrol Diri dengan Kecenderungan Berperilaku Agresif Siswa - Dewi Putri Resti; Riska Ahmad (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study aims to: (1) describe the aggressive behavior of students, (2) describe students' self-control abilities, (3) the significant test of the relationship between self-control and the tendency of students to behave aggressively. The type of research is quantitative with a descriptive correlational approach. The population of research was 475 students of Tanjung Mutiara 1 Senior High School, sampling using the Proportionate Stratified Random Sampling technique, and obtained a sample of 217 students. The instrument used is a questionnaire in the form of a Likert scale. The data obtained were analyzed using percentage techniques and to see the relationship between the two variables used the Pearson Product Moment Correlation technique. The research findings show that: (1) the tendency of aggressive behavior of students is in the high category, (2) self-control of students is in the moderate category, (3) there is a negative and significant relationship between self-control and the tendency to aggressively behave students with correlation coefficients -0.240 and a significance level of 0,000. This means that the higher the self control, the lower the tendency for students to behave aggressively. Conversely, the lower the self control, the higher the tendency of aggressive behavior of students